Tinjauan Kritis Simbol-simbol Budaya Nias dalam Iklan Produk Minuman Berenergi Studi Kasus Iklan Bermuatan Nilai Lokal Produk Kuku Bima Ener-G Versi “Ayo Wisata ke Sumatera” PT. Sido Muncul) - Ariel Sarototonafo; Widayatmoko Widayatmoko; Genep Sukendro (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2012)
Symbols of local culture especially Nias on TVC (Television Commercial) Kuku Bima Ener-G, version of “Let’s Travel to North Sumatra” from PT. Sidomuncul. Authors conducted a case study of the culture that campaigned Sidomuncul advertising through television media. The study was conducted using a critical research paradigm, which aim uncover Nias cultural symbols in the TVC of products Kuku Bima Ener-G PT Sidomuncul. The results suggested that the symbols used for Nias cultural values embodied in these symbols siding with the values espoused by Sidomuncul.